Exploring the Output Effect of Fiscal Policy Shocks in Low Income Countries - Honda, Jiro (IMF Working Papers; Working Paper ;, 2020)
What do we know about the output effects of fiscal policy in low income countries (LICs)? There are very few empirical studies on the subject. This paper fills this gap by estimating the output effects of government spending shocks in LICs. Our analysis-based on the local projection method-finds that the output effects in LICs are markedly lower than those in AEs and marginally smaller than those in EMs. We also find that in LICs, the output effects are larger (i) during recessions; (ii) under a fixed exchange rate regime; and/or (iii) with higher quality of institutions. Our analysis could not confirm any statistically significant output effect under floating exchange rate regimes. For the estimation of the output effects of fiscal spending shocks, it is thus important to consider the state of the economy and the country's structural characteristics. Our results imply that the output costs of fiscal adjustment in LICs may not be as large as previously thought, especially if adopted outside of a recession, based on cutting public consumption, and accompanied by reform to enhance institutions.